PROFIL GURU BAHASA INDONESIA DI PROPINSI BENGKULU - Muhammad Arifin (Universitas Bengkulu, 2016)
This study aimed at describing comprehensively the profile of Indonesian Language teachers in Bengkulu Province. The focus of the study were the educational background, school levels where the teachers currently teach, employment rank, gender, and age. Descriptive qualitative method was used in this research. From the data analysis, it is found that 98,97% of Indonesian Language teachers have bachelor degree; 65,64% of teachers teach in junior high school level; 34,96% of teachers are in Iva rank; 66,03% of teachers are female; and 89,76% of teachers are in the productive age (30-50 years-old).